2023
DOI: 10.3390/biology12020269
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Wild Food Plants Gathered by Ethnic Groups Living in Semi-Arid Region of Punjab, Pakistan

Abstract: Wild edible food plants (WFPs) are valuable resources in the traditional food systems of many local cultures worldwide, particularly in underdeveloped regions. Understanding patterns of food preferences requires conducting cross-cultural food studies among various ethnic groups in a specific area. In this context, the current study aimed to record WFP use among five ethnic groups in Punjab, Pakistan, by interviewing 175 informants selected through snowball sampling. The indicator food species for different eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Several workers reported that such a situation opens up opportunities for a new type of food system that supports the local traditional market [30,31]. If such situations create food shortages, peoples turn towards traditional foods and wild edible plants as an important available source of minerals and vitamins, and herbal ingredients [7][8]32,33].…”
Section: The Importance Of Weps As a Source Of Food And Nutritionmentioning
confidence: 99%
“…Several workers reported that such a situation opens up opportunities for a new type of food system that supports the local traditional market [30,31]. If such situations create food shortages, peoples turn towards traditional foods and wild edible plants as an important available source of minerals and vitamins, and herbal ingredients [7][8]32,33].…”
Section: The Importance Of Weps As a Source Of Food And Nutritionmentioning
confidence: 99%
“…In the secluded valleys of the Himalayas, local communities rely on natural resources, including plants, for their livelihoods, often migrating with their livestock to summer pastures in accordance with the changing seasons. They possess valuable knowledge regarding ecosystem services [ 13 ]. However, the intensive use of plants for medicinal purposes, grazing, and fodder has resulted in heightened pressure on plant biodiversity, thereby posing significant implications for the long-term sustainability of the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Pakistan is the fth most populous country in the world with > 240 million population and multi-ethnic region, culturally diverse, with cultural and dietary in uences from neighboring countries like Afghanistan and Iran predominating in the north and south western regions of the country and Indian in uences in the eastern regions. Moreover, Pakistan shares genetic characteristics with the Indian population due to historic large-scale population immigration from India to Pakistan during the Indian sub-continent partition in 1947 (17). Pakistan is one of the underrepresented countries for microbiome research in South Asia (18).…”
Section: Introductionmentioning
confidence: 99%